Estudo prospectivo das tecnologias em energia eólica: uma abordagem sobre turbinas eólicas - Cruz, Cleide Ane Barbosa da (2015)
Over the years, the need for electric energy production has increased exponentially is generated many environmental problems and climatic the planet. One way to reduce these impacts is extracted electricity production from clean sources of carbon dioxide emissions, such as wind, water, sun. The wind power option is part of a strategic policy of sustainable development that is emerging in recent years around the world. Thus, a survey based on patent search was carried out to thereby provide an overview of technological development related to wind turbines. The survey of patent documents was held in Espacenet base associating the terms Wind turbines AND Power AND generator, having returned 423 documents. It was noted the existence of deposits from the year 2000 until 2014, with more number of deposits in the years 2007, 2008, 2009, 2010, 2011, 2012, 2013 and 2014, with respectively, thirty-one, forty-one , fifty-two, fifty-four, fifty-five, fifty-four, fifty and twenty-five. The country with the most patent applications was China. Noteworthy is also that 67% of patent applications originate from individual inventors, 25% of companies and only 8% of universities.